Totality inside out : rethinking crisis and conflict under capital - Floyd, Kevin; Phillis, Jen Hedler, 1980-; Chandra, Sarika, 1969- (Fordham University Press, 2022)
"However divergent their analyses may be in other ways, some prominent anti-capitalist critics have remained critical of contemporary debates over reparative justice for groups historically oppressed and marginalized on the basis of race, gender, sexual identity, sexual preference, and/or ability, arguing that the most these struggles can hope to produce is a more diversity-friendly capital. Meanwhile, scholars of gender and sexuality as well as race and ethnic studies maintain that, by elevating the socioeconomic above other logics of domination, anti-capitalist thought fails to acknowledge specific forms and experiences of subjugation. The thinkers and activists who appear in Totality Inside Out reject this divisive logic altogether. Instead, they aim for a more expansive analysis of our contemporary moment to uncover connected sites of political struggle over racial and economic justice, materialist feminist and queer critique, climate change, and aesthetic value. The re-imagined account of capitalist totality that appears in this volume illuminates the material interlinkages between discrepant social phenomena, forms of oppression, and group histories, offering multiple entry points for readers who are interested in exploring how capitalism shapes integral relations within the social whole"--